Sustainable polycarbonate adhesives for dry and aqueous conditions with thermoresponsive properties - Anjeza Beharaj (Nature Portfolio, 2019)
Adhesives are ubiquitous in commodity products, however it it essential that their synthesis and degradation be sustainable without compromising their performance. Here, the authors report a library of adhesives based on environmentally benign building blocks that perform in both dry and wet environments.